Memanfaatkan Potensi Biodiversitas Daerah Jombang Jawa Timur untuk Membekalkan Nilai-Nilai Keberlanjutan dalam Pembelajaran Materi Keanekaragaman Hayati - Arum; Ulfi; Dwi; Reni; Agus; Andini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to describe and analyze the potential biodiversity of Jombang Regency that can be integrated into biology learning to equip students with sustainability values. The research method used was descriptive qualitative. The data sources consisted of: (1) biodiversity data from Jombang obtained from 18 articles resulting from student research projects selected using a purposive sampling technique; (2) biology learning profile data collected from 25 senior high school biology teachers from 13 schools in Jombang using snowball sampling; and (3) data from 20 articles obtained through a systematic literature review from Google Scholar and the SINTA portal using the keywords “biodiversity”, “environmental utilization”, and “biology learning”. The results showed that seven types of invertebrates and one type of vertebrate were found in various ecosystems, such as surrounding environments, gardens, parks, residential areas, rice fields, fields, ponds, and forests. These biodiversity resources have the potential to be utilized as learning resources and teaching materials, such as modules and booklets, to improve students’ knowledge, reading interest, learning motivation, critical thinking skills, biological literacy, and environmental awareness. In addition, biodiversity-based learning can also foster sustainability values, including critical thinking, systems thinking, self-awareness, collaboration, anticipatory competence, normative competence, strategic competence, and problem-solving skills in biology learning. The conclusion of this study indicates that biodiversity in Jombang has the potential to be utilized in biology learning as learning resources and teaching materials that enhance students’ skills while instilling sustainability values. This effort also supports the achievement of the Sustainable Development Goals (SDGs), particularly Goals 14 and 15.   Keywords: Biodiversity, Biology Learning, Jombang, Sustainability Values